(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Reformist authors in the West, most notably Scott Kugle, have called Islam’s prohibition of liwāṭ (sodomy) and other same-sex behavior into question. Kugle’s "Sexuality, Diversity, and Ethics in the Agenda of Progressive Muslims" (Progressive Muslims: 2003) and Homosexuality in Islam (2010) serve as the scholarly center for those who advocate sanctioning same-sex acts. Kugle traces the heritage of the Lot narrative’s exegesis to al-Tabari (d. 310/923), which, he contends, later exegetes came to regard as theologically axiomatic and thus beyond question. This study argues that Kugle’s critical methodological inconsistencies, misreading and misrepresentation of al-Tabari’s and other traditional works, as well as the anachronistic transposition of modern categories onto the classical sources, completely undermine his argument.